Առածների Ջիվանու գրական մշակումները - Թ. Գ. Պողոսյան (ՀՀ ԳԱԱ հրատ.)
Певцы-ашуги часто обращались к литературной обработке народных пословиц и басен. Пословицы созвучны дидактике ашугской поэзии, и ашуг Дживани, подвергая половицы литературной обработке, а порой переосмысляя, использовал их в своем творчестве, тем самым способствуя популяризации басен и пословиц. Bards have often addressed literary adaptations of national proverbs and fables. The proverbs are harmonious with the didactics of bard poetry, and Gusan Jivani used and sometimes revisited proverb adaptations in his work, thus contributing to their popularization.
Keywords: Literature; Language and Literature